Non-triglyceride components modulate the fat crystal network of palm kernel oil and coconut oil. (March 2018) - Chai, Xiuhang; Meng, Zong; Jiang, Jiang; Cao, Peirang; Liang, Xinyu; Piatko, Michael; Campbell, Shawn; Lo, Seong Koon; Liu, Yuanfa
Abstract: PKO and CNO are composed of 97–98% triacylglycerols and 2–3% minor non-triglyceride components (FFA, DAG and MAG). Triglycerides were separated from minor components by chromatographic method. The lipid composition, thermal properties, polymorphism, isothermal crystallization behavior, nanostructure and microstructure of PKO, PKO-TAG, CNO and CNO-TAG were evaluated. Removal of minor components had no effect on lipid composition and equilibrium solid fat contents. However, presence of minor components did increase the slip melting point and promoted the onset of crystallization from DSC crystallization profiles. The thickness of the nanoscale crystals increased with no polymorphic transformation after removing the minor components. Crystallization kinetics revealed that minor components decreased crystal growth rate with higher t 1/2 . Sharp changes in the values of the Avrami constant k and exponent n were observed for all fats around 10 °C. Increases in n around 10 °C indicated a change from one-dimensional to multi-dimensional growth. From the results of polarized light micrographs, the transformation from the coarser crystal structure to tiny crystal structure occurred in microstructure networks at the action of minor components. Graphical abstract: Highlights: Minor components influence crystallization kinetics of palm kernel oil (PKO) and coconut oil (CNO). Minor components accelerate early-stage of crystallization but suppress later growth. No influence on polymorphism after removal of the minor components The thickness of the nanoscale crystals increased after removal of the minor components.